Principles of Neural Information Processing - Seelen, Werner v.; Behrend, Konstantin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
In this fundamental book the authors devise a framework that describes the working of the brain as a whole. It presents a comprehensive introduction to the principles of Neural Information Processing as well as recent and authoritative research. The books´ guiding principles are the main purpose of neural activity, namely, to organize behavior to ensure survival, as well as the understanding of the evolutionary genesis of the brain. Among the developed principles and strategies belong self-organization of neural systems, flexibility, the active interpretation of the world by means of construction and prediction as well as their embedding into the world, all of which form the framework of the presented description. Since, in brains, their partial self-organization, the lifelong adaptation and their use of various methods of processing incoming information are all interconnected, the authors have chosen not only neurobiology and evolution theory as a basis for the elaboration of sucha framework, but also systems and signal theory. The most important message of the book and authors is: brains are evolved as a whole and a description of parts although necessary lets one miss the wood for the trees.
Introduction -- Evolution and Brain -- Function of the Overall System -- Structures in Neural Systems -- Aspects of Description -- Social Aspects - Remarks -- Remarks on Open Terms -- Options for Technical Feasibility -- A Viewpoint.
Keywords: Computational intelligence; Artificial intelligence; Neurosciences; Computational Intelligence; Artificial Intelligence; Neuroscience